2018
DOI: 10.2196/publichealth.7026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mobile Phone Text Message Reminders on Routine Immunization Uptake in Pakistan: Randomized Controlled Trial

Abstract: BackgroundImproved routine immunization (RI) coverage is recommended as the priority public health strategy to decrease vaccine-preventable diseases and eradicate polio in Pakistan and worldwide.ObjectiveThe objective of this study was to ascertain whether customized, automated, one-way text messaging (short message service, SMS) reminders delivered to caregivers via mobile phones when a child is due for an RI visit can improve vaccination uptake and timelines in Pakistan.MethodsThis was a randomized controlle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 35 publications
3
72
1
Order By: Relevance
“…The current study was not design to assess factors associated to low coverage but, other studies conducted in similar settings indexed parental ignorance, parental level of education, limitations due to geographical and cultural accessibility, outreach and door-to-door programs and poverty as key contributors to low immunization coverage [1][2][3]. Information and communication technology and incentives vaccination strategies for reminder has proven to be effective in improving childrens' access to EPI but have not been integrated in the routine EPI strategy [24][25][26][27][28][29]. On this note, the efficiency of these strategies should be assessed in the Cameroon context.…”
Section: Discussionmentioning
confidence: 95%
“…The current study was not design to assess factors associated to low coverage but, other studies conducted in similar settings indexed parental ignorance, parental level of education, limitations due to geographical and cultural accessibility, outreach and door-to-door programs and poverty as key contributors to low immunization coverage [1][2][3]. Information and communication technology and incentives vaccination strategies for reminder has proven to be effective in improving childrens' access to EPI but have not been integrated in the routine EPI strategy [24][25][26][27][28][29]. On this note, the efficiency of these strategies should be assessed in the Cameroon context.…”
Section: Discussionmentioning
confidence: 95%
“…Minimum detectable effect size (MDES): previous studies considered an effect size of 10%–20% as clinically significant and meaningful for public health decision makers 24 27 35. A priori, we selected a 15% difference among intervention and control groups as a meaningful outcome that would motivate policy makers to adapt and integrate the text message-based mHealth interventions in the existing EPI programme of Ethiopia.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Similarly, a 2016 Cochrane review found that information, education and outreach efforts work, but that evidence for the impact of monetary incentives is limited (Oyo-Ita et al 2016). A similarly mixed picture emerges for the impact of text message reminders on immunisation outcomes, and leads to the conclusion that there is limited high-quality evidence especially from low-and middle-income countries (Oliver-Williams et al 2017) and a call for better-powered studies (Kazi et al 2018).…”
Section: Contribution To the Literaturementioning
confidence: 99%